Validity of international ovarian tumour analysis simple rules in characterization of ovarian mass - K. P., Divya; Prabhu, Sujatha; B. S., Satish Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Ovarian malignancy is one of the most common cancer in women and is diagnosed at later stage in majority. The limiting factor for early diagnosis is lack of standardized terms and procedures in gynaecological sonography. Recently, IOTA simple rules have been externally validated to have an increased sensitivity and specificity in diagnosing ovarian malignancy. Methods: This is a prospective study in the Department of obstetrics and gynaecology conducted at ESIC-MC & PGIMSR Hospital, Bangalore from January 2020 to June 2021. 50 women diagnosed with ovarian mass and scheduled for surgery were admitted and evaluated for nature of ovarian mass using IOTA simple rules on ultrasonography and correlated with their histopathological diagnosis. Results: Among 50 ovarian masses, all 38 masses (76%) characterized as benign by IOTA simple rules were true benign (100%) on histopathological diagnosis. 10 masses (20%) characterized as malignant, 9 were true malignant and 1 was false malignant on histopathological diagnosis. 2 cases which were inconclusive by IOTA simple rules were characterized as benign on histopathological diagnosis. Thus in our study test sensitivity was 100%, specificity 97.56%, positive predictive value 90% and negative predictive value 100%. Conclusions: In clinical practice, IOTA simple rules as a diagnostic tool helps in characterization of most ovarian masses, which aids in optimal management and enhance better outcome. In ovarian masses for which the rules yielded an inconclusive results, subjective assessment by an experienced sonologist is advocatedd.